Development of a Novel mRNA Vaccine Against Pathotypes Causing Widespread Shigellosis Endemic: An In-Silico Immunoinformatic Approach - Abdur Razzak; Otun Saha; Khandokar Fahmida Sultana; Mohammad Ruhul Amin; Abdullah bin Zahid; Afroza Sultana; Uditi Paul Bristi; Sultana Rajia; Nikkon Sarker; Md Mizanur Rahaman; Newaz Mohammed Bahadur; Foysal Hossen (Bioinformatics and Biology Insights)
Shigellosis remains a major global health concern, particularly in regions with poor sanitation and limited access to clean water. This study used immunoinformatics and reverse vaccinology to design a potential mRNA vaccine targeting Shigella pathotypes out of 4071 proteins from Shigella sonnei str. Ss046, 4 key antigenic candidates were identified: putative outer membrane protein (Q3YZL0), PapC-like porin protein (Q3YZM5), putative fimbrial-like protein (Q3Z3I2), and lipopolysaccharide (LPS)-assembly protein LptD (Q3Z5V5), ensuring broad pathotype coverage. A multitope vaccine was designed incorporating cytotoxic T lymphocyte, helper T lymphocyte, and B-cell epitopes, linked with suitable linkers and adjuvants to enhance immunogenicity. Computational analyses predicted vaccine’s favorable antigenicity, solubility, and stability, while molecular docking and dynamic simulations demonstrated strong binding affinity and stability with Toll-like receptor 4 (TLR-4), indicating potential for robust immune activation. Immune simulations predicted strong humoral and cellular immune responses, characterized by significant cytokine production and long-term immune memory. Structural evaluations of the complex, including radius of gyration, root mean square deviation, root mean square fluctuation, and solvent accessibility, confirmed the vaccine’s structural integrity, and stability under physiological conditions. This research contributes to the ongoing effort to alleviate the global burden of Shigella infections, providing a foundation for future wet laboratory investigations aimed at vaccine development.